The relationship between work and education: transition in work and human formation in the context of Toyotism (Research, Society and Development, 2020)
This article seeks to analyze the dependence and autonomy of education at work, highlighting the historical context of the capitalist mode of production in the current model of work organization: Toyotism. The article was listed in four parts: the first, work as a foundation, in which it is analyzed how the human being jumps from the organic being to become a social being, later on, the interference of work in the current flexible education model is analyzed , then, we talked about human formation. And finally, we present in the final considerations a discussion on what is covered by flexible education. Our analysis uses the dialectical historical materialist method, as we understand that it is the method that most closely approximates the analysis of the concrete reality. The following theorists are included in the discussion: Antunes, Kuenzer, Lukács, Marx, Saviani and Tonet. They are authors of great importance in the academic environment, when referring to the ontological question of work, which presents continuities and discontinuities from one mode of production to the other.